Bibliometric Analysis with VOSviewer of Religious and Nationalistic Character Education through Extracurricular Activities in High School - Diny Aminaty; Santiani Santiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2025)
This study aims to analyze the trends and directions of research on religious character education and nationalism through extracurricular activities at the senior high school (SMA) level in Indonesia. The research employs a bibliometric approach using the Publish or Perish (PoP) and VOSviewer applications. Data were obtained from 100 articles indexed by Google Scholar and published between 2020 and 2025, using keywords such as character education, religious values, nationalism, extracurricular activities, and senior high school. The findings reveal that “character education” is the most dominant keyword and strongly connected to “religious values”, “nationalism”, and “extracurricular”. The co-word network visualization produced by VOSviewer indicates several clusters that demonstrate an integrated relationship between religious character education and nationalism, particularly through activities such as scouting and religious student organizations (Rohis). In addition, recent literature has begun to highlight themes such as the Profile of Pancasila Students, Pancasila values, and tolerance practices, suggesting a new direction in character education studies. These findings suggest that religious and national character education through extracurricular activities has become an important focus in Indonesia's educational development and holds significant potential for future research.